Optimal fabrication methods for miniature coplanar ion traps. (24th January 2018) - Decker, Trevor K.; Tian, Yuan; McClellan, Joshua S.; Bennett, Linsey; Lammert, Stephen A.; Austin, Daniel E.; Hawkins, Aaron R.
Abstract : Rationale: Ion trap mass spectrometers are beneficial due to their intrinsic sensitivity and specificity. Therefore, a portable version for in situ analysis of various compounds is very attractive. Miniaturization of ion traps is paramount for the portability of such mass spectrometers. Methods: We developed an optimized design for a planar linear ion trap mass spectrometer, consisting of two trapping plates with photolithographically patterned electrodes. Each plate is constructed using a machined glass substrate and standard microfabrication procedures. The plates are attached to a patterned circuit board via wire bonds then positioned approximately 5 mm apart. Results: Trapped ions are detected by ejecting them through tapered slits, which alleviate charge buildup. Mass analysis can be performed through either boundary or resonant ion ejection. Better than unit mass resolution is demonstrated with resonant ejection. Conclusions: The optimized planar linear ion trap provides good resolution and the potential for further miniaturization. This was accomplished by vigorously testing variables associated with ion trap design including electrical connections, substrate materials, and electrode designs.